On the role of public policies and wage formation for private investment in R&D: A long-run panel analysis - Tim Buyse; Freddy Heylen; Ruben Schoonackers (National Bank of Belgium, 2016)
This paper studies the drivers of business funded and performed R&D in a panel of 14 OECD countries since 1981. More specifically, we investigate the effects of public R&D related policies and wage formation. Following Pesaran (Econometrica, 2006) and Kapetanios et al. (Journal of Econometrics, 2011), our empirical strategy allows for cross-sectionally correlated error terms due to the presence of unobserved common factors, which are otentially non-stationary. We find that tax incentives are effective. Public funding (subsidization) of R&D performed by firms can also be effective if subsidies are not too low, neither too high. R&D performed within the government sector and within institutions of higher education is basically neutral with respect to business R&D. We find no evidence for crowding out, nor for complementarity. The higher education sector may, however, indirectly be of great significance. Our results reveal human capital accumulation at the tertiary level as a key driver of business R&D in the OECD during the last decades. As to the impact of wage formation, using an indicator for wage pres- sure developed by Blanchard (Economic Policy, 2006), we find that wage moderation may contribute to innovation, but only in fairly closed economies and in economies with flexible labour markets. In highly open economies and economies with rigid labour markets rather the opposite holds. In these economies high wage pressure may enhance creative destruction and force firms to innovate as a competitive strategy. Our results show that a careful treatment of the properties of the data is crucial.
Keywords: E22; J30; O31; O38; O57; 330; R&D; technology policy; wage formation; panel cointegration